A PERAN LPP TVRI SEBAGAI TELEVISI EDUKASI MELALUI PROGRAM BELAJAR DARI RUMAH SELAMA PANDEMI COVID-19: PERAN LPP TVRI SEBAGAI TELEVISI EDUKASI MELALUI PROGRAM BELAJAR DARI RUMAH SELAMA PANDEMI COVID-19 - Rachmaria, Laksmi (DIALEKTIKA KOMUNIKA: Jurnal Kajian Komunikasi dan Pembangunan Daerah, 2021)
This research started from an interest in TVRI as a public media to help the public related to the condition of distance education during the COVID-19 pandemic, which during this pandemic makes everyone in the world, especially in Indonesia, require all activities carried out at home, one of which is learning. The problem in this research is how LPP TVRI Role as Educational Television Through Home Learning Program During THE COVID-19 Pandemic. The research paradigm used is post-positivism with qualitative approach and descriptive method. Data obtained through in-depth interviews and documentation such as photographs, personal documents and official documents to be used as supporting data on this research. Problems are analyzed using the function of mass communication. The results showed that LPP TVRI is able to provide quality content and learning materials to be aired to the community, especially school children through the Learning from Home program. This can be achieved because of the role of supervision, interpretation, relationships, and the dissemination of values. The conclusions in this study are from the four indicators drawn from the function of mass communication that LPP TVRI has a role in the supervision of broadcast content, interpretation in the dissemination of audience insights, relationships in uniting indonesian society in an educational impression, as well as the spread of noble values implied and express in the content of Learning from Home.